Integrated assessment of MIG welding parameters on carbon steel using RSM optimization - Junita, Mohd Said (2023)
This study focused on the influence of parameter optimization of MIG welding on material properties and weld quality through flexural strength and weld bead geometry through experimental design. Structural testing shows that metal failure is often caused by imperfections in the weld pool, particularly in welded joints. Due to incorrect selection of the chosen welding parameters, weldability of the material and metal forming, they contribute to defects and require the post-treatment process. Therefore, the objective of this study is to minimize defects in welds and maximize the material strength of welded parts by using a fully quadratic second-order regression model to predict selected optimal process parameters. The JIS G3131 hot-rolled carbon steel material selected for this study is based on its extensive use as automotive parts, has economic value, and is suitable for welding. The experimental welding process is a MIG butt weld joint according to AWS 1.1 standards. The experimental tests correspond to the 3 x 3 orthogonal array of the RSM design; the process parameters are welding current, arc voltage and welding speed and their responses are bead height, bead width, penetration, and flexural strength. Non-destructive testing X-ray radiography is performed to see the flaw in the weld pool. The durability of the welded connection is then determined using a three-point bending test. Design experiments are implemented to obtain an optimal combination of input parameters with a 95% confidence level. An experimental design based on an orthogonal array and analysis of variance (ANOVA) is also used in this study. Its contribution to each factor and the regression analysis. The predicted flexural strength was determined to be 903.1 MPa with an error of 0.66% compared to the experimental value of 897 MPa. Additional predicted values for weld penetration, bead width, and bead height of 3.01, 9.45, and 2.04, respectively. In addition, in an RT inspection test, it was also found that the test sample by optimum parameter had no defect in the welded joint. For the regression analysis of the RSM combination, the optimal parameter values are 115, 20, and 18 for current, speed, and voltage. Confirmation tests for DT and NDT, were also performed after the optimal parameter determination to validate the optimal parameter settings. This research concludes that the optimal use of process parameters for welded products has improved weld geometry and flexural strength, which this optimization method is widely used and valuable in metal fabrication.